2001
DOI: 10.1577/1548-8675(2001)021<0269:sefmyc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Survival Estimates for Migrant Yearling Chinook Salmon and Steelhead Tagged with Passive Integrated Transponders in the Lower Snake and Lower Columbia Rivers, 1993–1998

Abstract: Precise, up-to-date survival estimates for salmonids that migrate through reservoirs, hydroelectric dams, and free-flowing sections of the Snake and Columbia rivers are essential to develop effective strategies for recovering depressed stocks. To provide this information, survival was estimated for yearling chinook salmon Oncorhynchus tshawytscha and steelhead O. mykiss with passive integrated transponder (PIT) tags that migrated through Snake River dams and reservoirs from 1993 through 1998. A multiple-recapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 25 publications
5
95
0
1
Order By: Relevance
“…When estimates for a particular river section or passage route were available from more than one release group, the estimates were often combined using a weighted average (Muir et al 2001a). Weights were inversely proportional to the respective estimated relative variance (coefficient of variation squared).…”
Section: Survival Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…When estimates for a particular river section or passage route were available from more than one release group, the estimates were often combined using a weighted average (Muir et al 2001a). Weights were inversely proportional to the respective estimated relative variance (coefficient of variation squared).…”
Section: Survival Estimationmentioning
confidence: 99%
“…Evaluations using paired releases of PIT tagged smolts into the bypass and tailrace at each dam found little or no evidence of post-detection mortality (Muir et al 2001a). However, no such evaluation has been conducted at John Day Dam to test this assumption, partly because no mortality was found experimentally at upstream dams, and partly because the lack of sufficient PIT-tag detection capabilities downstream from John Day Dam would require prohibitively large sample sizes.…”
Section: Estimates Of Proportion Of Population Transportedmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated individual-based models for data analysis were also developed (Burnham et al 1987) and applied, using PIT tags, to monitor juvenile salmonid survival and migration timing in the Columbia River basin (Skalski et al 1998;Muir et al 2001;Budy et al 2002). More recently, PIT tags have been used to estimate adult salmonid survivals in the Columbia River (Berggren et al 2003(Berggren et al , 2005Williams et al 2005;Copeland et al 2007).…”
mentioning
confidence: 99%
“…Some researchers (e.g., Bouwes et al 1999) concluded that passing a dam by the bypass system has a negative effect on survival, in contradiction to the CJS assumptions. On the other hand, Muir et al (2001) found no significant effect of upstream detection (bypass) on downstream juvenile survival and detection for migrating yearling Chinook salmon and steelhead from 1993 through 1998. Also, Smith et al (1998) found no significant effect on downstream juvenile survival and detection of delayed migration caused by passing a dam through the bypass system.…”
Section: Methodsmentioning
confidence: 94%